THE ANALYSIS OF BEEF CATTLE SUBSYSTEM AGRIBUSINESS IMPLEMENTATION IN CENTRAL JAVA PROVINCE, INDONESIA - Ekowati, T.; Darwanto, D.H.; Nurtini, S.; Suryantini, A. (Diponegoro University, 2011)
The study aimed to analyze the implementation of subsystem agribusiness on the beef cattlefarming in Central Java. Five districts (Rembang, Blora, Grobogan, Boyolali and Wonogiri) werepurposively chosen based on the value of Location Quotient (LQ). The study was conducted usingquota sampling method. Forty respondents of each district were chosen randomly using quota sampling.Data were analyzed through Structural Equation Model (SEM). The results showed that each subsystemagribusiness had adequate potential score. The score of 0.693, 0.721, 0.684, 0.626, and 0.691 were givenfor up-stream subsystem, on-farm, down-stream subsystem, marketing and supporting institution,respectively. The results showed that the SEM model was feasible with Chi-Square value=0.952;RMSEA=0.000; Probability =0.621 and TL1=1.126. The significant results of Critical Ratio (CR) were:up-stream subsystem to the on-farm agribusiness; on-farm subsystem to down-stream agribusiness;down-stream subsystem to the farmer’s income; marketing subsystem to the up-stream agribusiness andSupporting Institution to the marketing subsystem and down-stream agribusiness. The conclusion ofresearch indicated that the implementation of beef cattle subsystem agribusiness had adequate index andgive positive effect to the beef cattle agribusiness.